Roles of KH. Abdul Wahab Sya'roni and Syaikh Ali bin Ahmad Basalamah in the Development of Thariqoh Tijaniyah in Jatibarang, Brebes, Central Java - Mustain Yusuf; Yety Rochwulaningsih; Singgih Tri Sulistiyono (Indonesian Historical Studies, 2017)
The main purpose of this article is to examine the roles of K.H. Abdul Wahab Sya'roni and Shaykh Ali bin Ahmad Basalamah in the development of Thariqoh At-Tijaniyah in Jatibarang Brebes, Central Java Province. This discussion is very interesting given that this thoriqoh is developing in the spreading area of other thariqoh that is Thariqoh Qoodiriyah Naqsyabandiyah. Therefore, its spreading faces some challenges. The spread of Thariqoh At-Tijaniyah in Jatibarang Brebes cannot be separated from the critical roles of Kyai Sya'roni and Shaykh Ali bin Ahmad Basalamah. In the beginning, these two ulamas pioneered the establishment and development of thariqoh which is not only bounded to Jatibarang Brebes but also widen to the neighboring areas, especially in the Northern Coast of Java (Pantura). Nevertheless, the next development of this thariqoh is centered in Jatibarang, Brebes. Regarding to this matter, the development of Thariqoh At-Tijaniyah especially in Brebes and the roles of these kyai will be discussed.